Modeling of cross line operation of urban rail transit trains based on passenger travel time - LUO Qin; LIN Bin; GU Mengqi; YANG Liang; ZHANG Xiaochun (Shenzhen Daxue xuebao. Ligong ban)
Cross line operation mode of urban rail transit can not only meet diversified travel needs of passengers and improve efficiency of passenger travel, but also shorten the time and space distance between suburban and urban core areas. In this paper, the travel time cost of different types of passengers is analyzed on the basis of considering the train selection probability for passengers to choose cross train or transfer. An optimization model of cross line operation organization is established with the objective function of minimizing the total travel time cost of passengers. The model is solved by genetic algorithm. The scheme of metro Line Ⅰ of city S crossing into Line Ⅱ is used as an example to verify the feasibility of the model, and the optimal train density under different train load rates is obtained. This study can provide a reference for the cross line operation organization of urban rail transit.